Drain or no drain in Rhomboid excision and Limberg rotational flap for pilonidal sinus - Joshi, Arbin; Acharya, Bigyan (Journal of Kathmandu Medical College, 2021)
Background: Healing in Rhomboid flap for pilonidal sinus is always a problem. Different measures are applied to reduce the rate of wound infection with variable results. Objectives: To determine the effect of routine use of drain on the rate of early wound complications and additional interventions after Rhomboid flap. Methods: A retrospective chart review of all cases that underwent Rhomboid flap in five years in two tertiary care centres was done. Complication rates such as wound infection, wound disruption, and flap necrosis were evaluated. Results: A total of 38 cases of Rhomboid flap are included for analysis. Out of all cases 37 cases were done for Pilonidal sinus and one case for presacral dermoid cyst. In the first eight cases, flap was made without drain and subsequent 30 cases were done with two suction drains for five days. The rate of superficial wound infection in the group without drain was found to be significantly higher compared with flap with drain 5 (in 8) versus 2 (in 30) (62.5% versus 6.66%, p <0.5). Conclusion: Drain placement after Rhomboid flap is a good intervention to reduce wound infection.